2022
DOI: 10.3390/ma15196525
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and Photo-Induced Effects of Different Types of N-Doped Graphene Quantum Dots

Abstract: Due to the increasing number of bacterial infections and the development of resistivity toward antibiotics, new materials and approaches for treatments must be urgently developed. The production of new materials should be ecologically friendly considering overall pollution with chemicals and economically acceptable and accessible to the wide population. Thus, the possibility of using biocompatible graphene quantum dots (GQDs) as an agent in photodynamic therapy was studied. First, dots were obtained using elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…31 Moreover, some studies have reported that defects induced heteroatom doping, such as nitrogen and sulfur dopants, can reduce the band gap of GQDs, leading to improve light absorption and prolonged luminescence lifetime. 24,[32][33][34][35][36][37][38] In addition, the presence of defects in GQDs has been exploited for specic applications. For example, Wang et al develop a carbon-based non-metallic catalyst using defect-rich GQDs, and the catalytic performance of this catalyst depends on the defect density, showing potential for anti-cancer applications.…”
Section: Introductionmentioning
confidence: 99%
“…31 Moreover, some studies have reported that defects induced heteroatom doping, such as nitrogen and sulfur dopants, can reduce the band gap of GQDs, leading to improve light absorption and prolonged luminescence lifetime. 24,[32][33][34][35][36][37][38] In addition, the presence of defects in GQDs has been exploited for specic applications. For example, Wang et al develop a carbon-based non-metallic catalyst using defect-rich GQDs, and the catalytic performance of this catalyst depends on the defect density, showing potential for anti-cancer applications.…”
Section: Introductionmentioning
confidence: 99%